Use of AI-based Banking Applications for Customer Service - Junaedi, Achmad Tavip; Suhardjo, Suhardjo; Andi, Andi; Putri, Novita Yulia; Hutahuruk, Marice Br; Renaldo, Nicholas; Musa, Sulaiman; Cecilia, Cecilia (First Ciera Publisher, 2024)
This paper explores the state-of-the-art advancements in AI-based banking applications and their impact on customer service, focusing on their capabilities, benefits, and potential challenges. The descriptive qualitative method is used to examine real-world applications of AI in banking, focusing on their operational mechanisms and influence on customer experiences. The data analysis process involves the following steps: Thematic Analysis, Comparative Analysis, and Content Analysis. AI technologies such as chatbots, virtual assistants, and fraud detection systems enhance operational efficiency, provide personalized experiences, and improve security in banking. AI-based banking applications have significantly enhanced customer service by improving operational efficiency, personalization, and security, leading to higher customer satisfaction. Future research can investigate frameworks for ensuring fairness, transparency, and accountability in AI-driven customer service systems.